2016
DOI: 10.3164/jcbn.16-43
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of gastric cancer detected within 1 year after successful eradication of <i>Helicobacter pylori</i>

Abstract: Gastric cancers are sometimes diagnosed in patients who have successfully undergone Helicobacter pylori (H. pylori) eradication. We analyzed the clinicopathological features of gastric cancers detected after eradication to clarify their characteristics. We reviewed 31 patients with 34 cases of gastric cancer detected after successful H. pylori eradication. Clinicopathological characteristics analyzed included interval since eradication, interval since last endoscopy, tumor size, and depth of invasion. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 29 publications
2
32
0
1
Order By: Relevance
“…No significant differences were noted in the histopathological types of the eradicated and non-eradicated cancers, and this result was consistent with previous reports [11, 14, 22, 25, 26]. Additionally, independently of the eradication status, a gastrointestinal phenotype was observed more often than the gastric, intestinal, and null phenotypes in our analysis.…”
Section: Discussionsupporting
confidence: 82%
“…No significant differences were noted in the histopathological types of the eradicated and non-eradicated cancers, and this result was consistent with previous reports [11, 14, 22, 25, 26]. Additionally, independently of the eradication status, a gastrointestinal phenotype was observed more often than the gastric, intestinal, and null phenotypes in our analysis.…”
Section: Discussionsupporting
confidence: 82%
“…Surgery and endoscopic resection at an early stage is still the only chance for cure . Although it has been reported that H. pylori eradication therapy reduces the incidence of gastric cancer and is widely conducted to prevent gastric carcinogenesis, gastric cancers are still diagnosed in patients who received successful eradication therapy . Thus, endoscopic surveillance of gastric cancers after H. pylori eradication is expected to be a beneficial approach for detection.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Although it has been reported that H. pylori eradication therapy reduces the incidence of gastric cancer and is widely conducted to prevent gastric carcinogenesis, gastric cancers are still diagnosed in patients who received successful eradication therapy. [9][10][11][12][13] Thus, endoscopic surveillance of gastric cancers after H. pylori eradication is expected to be a beneficial approach for detection. The endoscopic and histological features of gastric cancers after eradication have been investigated vigorously.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that the incidence of primary EGC increases 5 years after H pylori has been eradicated . Moreover, this new form has been observed not only in MGC but also in primary EGC after H pylori eradication (Figure ) …”
Section: Can H Pylori Treatment Reduce the Incidence Of Gastric Cancer?mentioning
confidence: 69%
“…21 Moreover, this new form has been observed not only in MGC but also in primary EGC after H pylori eradication (Figure 4). [22][23][24][25] Because this form of EGC is different from that of gastric cancer that occurs in the conventional H pylori-infected stomach, there is a possibility that this form of cancer may be misdiagnosed or diagnosed after it has progressed to a later stage. In addition, the belief among endoscopists that gastric cancer is less likely to develop after H pylori eradication may lead to a detection bias.…”
Section: Latent Gastric Cancer After H Pylori Eradicationmentioning
confidence: 99%